The Expansion of Palm Oil Plantation and the Crisis of Orangutan Habitat in Indonesia: A Literature Review - Altaf, Carissa; Suranto, Suranto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Indonesia is the country with the best biodiversity in the world, as measured by its terrestrial and marine biodiversity. However, at the same time, there is additionally a significant decline in biodiversity. One species experiencing population decline is the orangutan, because of the growth of oil palm plantations that convert natural forests, resulting in the loss and fragmentation of orangutan habitats. This paper aims to analyze the effect of oil palm plantation expansion at the orangutan habitat crisis in Indonesia. This paper uses a literature review method with a descriptive-qualitative approach, drawing on scientific journals, conservation organization reports, and official government documents. Data are analyzed descriptively and analytically to study the relationship between oil palm plantation growth and orangutan habitat. The outcomes of the study indicate that orangutans are noticeably depending on the complexity of natural forests for nesting and foraging. Forest conversion to homogeneous monoculture oil palm plantations reduces habitat and food sources and increases conflict between humans and orangutans. This has caused a decline within the orangutan population, resulting in its categorization as a critically endangered species. The weak implementation of oil palm plantation management and orangutan conservation policies further exacerbates the crisis of the orangutan habitat. Therefore, efforts to strengthen integrated palm oil plantation governance and orangutan conservation based on ecosystem restoration are crucial.